2015
DOI: 10.48550/arxiv.1503.07303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GRAVITY: the VLTI 4-beam combiner for narrow-angle astrometry and interferometric imaging

Abstract: GRAVITY is the second generation Very Large Telescope Interferometer instrument for precision narrow-angle astrometry and interferometric imaging in the Near Infra-Red (NIR). It shall provide precision astrometry of order 10 microarcseconds, and imaging capability at a few milliarcsecond resolution, and hence will revolutionise dynamical measurements of celestial objects. GRAVITY is currently in the last stages of its integration and tests in Garching at MPE, and will be delivered to the VLT Interferometer (VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…We expect that future observations of trajectories of bright stars near the Galactic Center like GRAVITY [113], E-ELT [114] and TMT [115] will realize our forecasts and improve the current graviton mass constraints.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that future observations of trajectories of bright stars near the Galactic Center like GRAVITY [113], E-ELT [114] and TMT [115] will realize our forecasts and improve the current graviton mass constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that Reissner -Nordström metric is a rather natural solution in Horndeski gravity [71] and in this case Q 2 parameter reflects an interaction with a scalar field and it could be also negative similarly to a tidal charge. In paper [71] it was expressed an opinion that the hairy black hole solutions look rather realistic and these objects could exist in centers of galaxies and if such objects (hairy black holes in Horndeski gravity) exist in nature, in particular in the Galactic Center, current and future advanced facilities such as GRAVITY [72], E-ELT [73], TMT [74] etc. may be very useful to detect signatures of black hole hairs of an additional dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Planned observations of trajectories of bright stars near the Galactic Center with GRAV-ITY [57], E-ELT [58] and TMT [59] may improve the discussed estimates of graviton masses.…”
Section: Discussionmentioning
confidence: 99%